The potential role of alternative dispute resolution for intellectual property disputes in Qatar - Ahmed Essa Al Sulaiti (22996102) (2025)
Alternative dispute resolution (ADR) has become an essential tool for resolving IP disputes, offering faster, cost-effective and flexible procedures that enhance commercial predictability while reducing litigation burdens. However, ADR alone does not guarantee effective access to justice, a core principle of Sustainable Development Goal 16.3. This article argues that ensuring meaningful access to justice in IP disputes requires moving beyond traditional arbitration and mediation towards an integrated legal and technological framework. Innovations such as online dispute resolution and decentralized arbitration improve accessibility, expedite proceedings and lower costs in cross-border disputes. A structured institutional framework is needed to embed ADR within a coherent legal system. Qatar offers a compelling case study, given its cultural emphasis on amicable settlement and mediation, rooted in the Arab legal tradition. By integrating indigenous dispute resolution methods with digital technologies, Qatar can develop an ADR model that aligns with international best practices while enhancing justice in IP disputes. Other Information Published in: Journal of Intellectual Property Law & Practice License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/jiplp/jpaf062